A beamforming-based joint estimation method for gas pipeline leak localization. (June 2021) - Zheng, Xiaoliang; Wang, Qiang; Xue, Sheng; Zheng, Chunshan
Highlights: The new method estimates leak locations and wave velocities jointly. Multipath jamming under experimental environment were reduced. The new method has better accuracy and antijamming capability than the existing one. Abstract: This paper proposes a beamforming-based joint estimation method to improve the accuracy and robustness of the localization method that measures acoustic signals caused by gas pipeline leaks. The anti-interference capability of the new method is enhanced with the help of spatial filtering using a beamforming algorithm and a linear array. Joint estimations for leak locations and wave velocities allow the new method to ignore the requests for prior knowledge of wave velocity. The mean absolute percentage error (MAPE) of the joint estimation method using a seven-sensor linear array was reduced by 68.7% and 53.7% compared to the MAPEs of the cross-correlation method, which used the theoretical velocity of 1800 m/s and the velocity estimated through the new method, respectively. The tests also indicate that the joint estimation method has better anti-interference capabilities, of which the MAPEs remained less than 3% in the SNR range from −15 dB to 0 dB.